Serological investigation of HIV infections, HBsAg and syphilis in prostitutes in Elazig - Orak, S.; Dalkiliç, A.E.; Ozbal, Y. (My University, 1991)
It is well known that the infections of AIDS, serum hepatitis and syphilis were transmitted by sexual contact. The sera of 66 prostitutes were investigated for determination of anti-HIV by ELISA, HBsAg by IHA and antibodies to syphilis by TPH methods in area of Elazig. The anti-HIV antibodies could not be detected in prostitutes, but HBsAg was positive in 13 (19.7%) and antibodies to syphilis was positive in 6 (9.1%) of total.
Elazig'daki hayat kadinlarinin HIV, HBsAg ve sifilis yönünden serolojik incelenmesi.
Keywords: Acquired Immunodeficiency Syndrome; Antibodies, Bacterial; Enzyme-Linked Immunosorbent Assay; Female; Hemagglutination Tests; Hepatitis B; Hepatitis B Surface Antigens; HIV Antibodies; Humans; Prostitution; Sexually Transmitted Diseases; Syphilis; Syphilis Serodiagnosis; Treponema pallidum; Turkey; bacterium antibody; hepatitis B surface antigen; Human immunodeficiency virus antibody; acquired immune deficiency syndrome; article; blood; enzyme linked immunosorbent assay; female; hemagglutination test; hepatitis B; human; immunology; prostitution; sexually transmitted disease; syphilis; syphilis serology; Treponema pallidum; Turkey (republic)